2011
DOI: 10.1080/17439760.2011.558848
|View full text |Cite
|
Sign up to set email alerts
|

Death and gratitude: Death reflection enhances gratitude

Abstract: Although gratitude is important to the good life, little is known about factors that enhance gratitude. Some have suggested that traumatic events such as near-death experiences and life-threatening illnesses might enhance gratitude. If reflecting on death causes one to appreciate life as a limited resource, this might enhance gratitude. This study investigated this theory. Participants were randomly assigned to a death reflection condition, a traditional mortality salience condition, or to a control condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 32 publications
1
61
1
3
Order By: Relevance
“…Incluso cómo el reflexionar sobre la muerte aumenta la gratitud (Frias, Watkins, Webber y Froh, 2011).…”
Section: Las Fortalezas Y El Estado De Bienestarunclassified
“…Incluso cómo el reflexionar sobre la muerte aumenta la gratitud (Frias, Watkins, Webber y Froh, 2011).…”
Section: Las Fortalezas Y El Estado De Bienestarunclassified
“…Lambert et al (2009) showed that experimentally induced appreciative functioning can lead to a response of higher life satisfaction, in contrast with experimentally induced envy. In a cross-sectional design, Froh et al (2011) found that appreciative functioning was negatively correlated with envy. Hence, it may be that appreciative functioning both promotes contentment and counteracts opposing emotions such as envy.…”
Section: The Emotions Domainmentioning
confidence: 99%
“…Positive counter-factual thinking involves constructing alternative situations against which a person's real situation can be appraised as more valuable, thus prompting gratefulness. For example, Frias et al (2011) found that contemplation of death, a negative alternative, enhanced gratefulness for life. Counter-factual thinking may allow people to creatively generate benefit appraisals.…”
Section: The Comprehension and Coping Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging experimental evidence that specific and individuated mortality awareness manipulations, which are thought to facilitate open and authentic considerations of death (i.e., death reflection), can generate increased desires for intrinsic striving and more prosocial behavior, compared to unspecific and abstract mortality salience manipulations (Cozzolino, Staples, Samboceti, & Meyers, 2004;Blackie & Cozzolino, 2011;Frias, Watkins, Webber, & Froh, 2011;Cozzolino, Blackie, Rentzelas, Geeraert, & Meyers, 2012). Despite this experimental evidence, however, we are unaware of research that has explicitly explored positive components of the self (e.g., esteem, self-concept clarity, existential well-being) as a function of the interaction between self-reported levels of death fear and death denial.…”
Section: "…The Paradox Became Clearer and Clearer Death Destroys A Mmentioning
confidence: 99%